-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathcat-prop.tex
2488 lines (2038 loc) · 111 KB
/
cat-prop.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
366
367
368
369
370
371
372
373
374
375
376
377
378
379
380
381
382
383
384
385
386
387
388
389
390
391
392
393
394
395
396
397
398
399
400
401
402
403
404
405
406
407
408
409
410
411
412
413
414
415
416
417
418
419
420
421
422
423
424
425
426
427
428
429
430
431
432
433
434
435
436
437
438
439
440
441
442
443
444
445
446
447
448
449
450
451
452
453
454
455
456
457
458
459
460
461
462
463
464
465
466
467
468
469
470
471
472
473
474
475
476
477
478
479
480
481
482
483
484
485
486
487
488
489
490
491
492
493
494
495
496
497
498
499
500
501
502
503
504
505
506
507
508
509
510
511
512
513
514
515
516
517
518
519
520
521
522
523
524
525
526
527
528
529
530
531
532
533
534
535
536
537
538
539
540
541
542
543
544
545
546
547
548
549
550
551
552
553
554
555
556
557
558
559
560
561
562
563
564
565
566
567
568
569
570
571
572
573
574
575
576
577
578
579
580
581
582
583
584
585
586
587
588
589
590
591
592
593
594
595
596
597
598
599
600
601
602
603
604
605
606
607
608
609
610
611
612
613
614
615
616
617
618
619
620
621
622
623
624
625
626
627
628
629
630
631
632
633
634
635
636
637
638
639
640
641
642
643
644
645
646
647
648
649
650
651
652
653
654
655
656
657
658
659
660
661
662
663
664
665
666
667
668
669
670
671
672
673
674
675
676
677
678
679
680
681
682
683
684
685
686
687
688
689
690
691
692
693
694
695
696
697
698
699
700
701
702
703
704
705
706
707
708
709
710
711
712
713
714
715
716
717
718
719
720
721
722
723
724
725
726
727
728
729
730
731
732
733
734
735
736
737
738
739
740
741
742
743
744
745
746
747
748
749
750
751
752
753
754
755
756
757
758
759
760
761
762
763
764
765
766
767
768
769
770
771
772
773
774
775
776
777
778
779
780
781
782
783
784
785
786
787
788
789
790
791
792
793
794
795
796
797
798
799
800
801
802
803
804
805
806
807
808
809
810
811
812
813
814
815
816
817
818
819
820
821
822
823
824
825
826
827
828
829
830
831
832
833
834
835
836
837
838
839
840
841
842
843
844
845
846
847
848
849
850
851
852
853
854
855
856
857
858
859
860
861
862
863
864
865
866
867
868
869
870
871
872
873
874
875
876
877
878
879
880
881
882
883
884
885
886
887
888
889
890
891
892
893
894
895
896
897
898
899
900
901
902
903
904
905
906
907
908
909
910
911
912
913
914
915
916
917
918
919
920
921
922
923
924
925
926
927
928
929
930
931
932
933
934
935
936
937
938
939
940
941
942
943
944
945
946
947
948
949
950
951
952
953
954
955
956
957
958
959
960
961
962
963
964
965
966
967
968
969
970
971
972
973
974
975
976
977
978
979
980
981
982
983
984
985
986
987
988
989
990
991
992
993
994
995
996
997
998
999
1000
% \documentclass[11pt,toc,fleqn]{article}
% \usepackage{array,multirow,amsthm,amsmath,amssymb,url}
% % \usepackage{bussproofs}
% % \usepackage{showlabels}
% \usepackage{natbib}
% \usepackage{mathrsfs}
% \usepackage{tikz-cd}
% \newtheorem{prop}{Proposition}[section]
% \newtheorem{lemma}[prop]{Lemma}
% \newtheorem{thm}[prop]{Theorem}
% \newtheorem{cor}[prop]{Corollary}
% \newtheorem{conj}[prop]{Conjecture}
% \newtheorem{fact}[prop]{Fact}
% % \newtheorem*{stone}{Stone Duality Theorem}
% \theoremstyle{definition}
% \newtheorem*{defn}{Definition}
% \newtheorem*{exercise}{Exercise}
% \newtheorem*{exercises}{Exercises}
% \newtheorem*{example}{Example}
% \newtheorem*{remark}{Remark}
% \theoremstyle{remark}
% \newtheorem*{disc}{Discussion}
% \newtheorem*{note}{Note}
% \author{Hans Halvorson}
% \date{\today}
% \newcommand{\RA}{\vdash}
% \newcommand{\7}{\mathbb}
% \newcommand{\2}{\mathscr}
% \newcommand{\lra}{\leftrightarrow}
% \newcommand{\cat}[1]{\mathbf{#1}}
% \renewcommand{\emph}{\textbf}
% \newcommand{\monic}{\rightarrowtail}
% \newcommand{\epi}{\twoheadrightarrow}
% \usepackage[framemethod=TikZ]{mdframed}
% \newcounter{axi}\setcounter{axi}{0}
%
% \begin{document}
\chapter{The Category of Propositional Theories} \label{cat-prop}
%% further reading: Just and Weese, Discovering Modern Set Theory, vol 2
%% http://plato.stanford.edu/entries/boolalg-math/
%% high priority: in Stone, epi are surjective
%% TO DO: show existence of generator and co-generator in $\cat{Th}$.
%% The generator is the empty theory in signature { p}.
One of the primary goals of this book is to provide a formal model of
``the universe of all scientific theories.'' Now, in the 20th
century, mathematics stepped up another level of abstraction, and it
began to talk of structured collections of mathematical objects ---
e.g.\ the category of groups, topological spaces, manifolds, Hilbert
spaces, or sets. This maneuver can be a little bit challenging for
foundationally oriented thinkers, viz.\ philosophers, because we are
now asked to consider collections that are bigger than any set.
However, mathematicians know very well how to proceed in this manner
without falling into contradictions (e.g.\ by availing themselves of
Grothendieck universes).
We want to follow the lead of the mathematicians, but instead of
talking about the category of groups, or manifolds, or Hilbert spaces,
etc., we want to talk about the category of all {\it theories}. In
the present chapter we work out one special case: the category of all
propositional theories. Of course, this category is too simple to
serve as a good model for the category of all scientific theories.
However, already for predicate logic, the category of theories becomes
extremely complex, almost to the point of mathematical intractability.
In subsequent chapters, we will make some headway with that case; for
the remainder of this chapter, we restrict ourselves to the
propositional case.
After defining the relevant category $\mathbf{Th}$ of propositional
theories, we will show that $\mathbf{Th}$ is equivalent to the
category $\cat{Bool}$ of Boolean algebras. We then prove a version of
the famous Stone duality theorem, which shows that $\cat{Bool}$ is
dual to a certain category $\cat{Stone}$ of topological spaces. This
duality shows that each propositional theory corresponds to a unique
topological space, viz.\ the space of its models; and each translation
between theories corresponds to a continuous mapping between their
spaces of models.
\section{Basics}
\newcommand{\sg}{\mathsf{Sent}(\Sigma )}
\begin{defn} We let $\mathbf{Th}$ denote the category whose objects
are propositional theories, and whose arrows are translations
between theories. We say that two translations
$f,g:T\rightrightarrows T'$ are equal, written $f=g$, just in case
$T'\vdash f(\phi )\leftrightarrow g(\phi )$ for every $\phi\in\sg$.
[Note well: equality between translations is weaker than
set-theoretic equality.] \end{defn}
\begin{defn} We say that a translation $f:T\to T'$ is
\emph{conservative} just in case: for any
$\phi\in\mathsf{Sent}(\Sigma )$, if $T'\vdash f(\phi )$ then
$T\vdash \phi$. \end{defn}
\begin{prop} A translation $f:T\to T'$ is conservative if and only if
$f$ is a monomorphism in the category
$\cat{Th}$. \label{test} \end{prop}
\begin{proof} Suppose first that $f$ is conservative, and let
$g,h:T''\to T$ be translations such that $f\circ g=f\circ h$. That
is, $T'\vdash fg(\phi )\leftrightarrow fh(\phi )$ for every sentence
$\phi$ of $\Sigma ''$. Since $f$ is conservative, $T\vdash g(\phi
)\leftrightarrow h(\phi )$ for every sentence $\phi$ of $\Sigma ''$.
Thus, $g=h$, and $f$ is a monomorphism in $\cat{Th}$.
Conversely, suppose that $f$ is a monomorphism in the category
$\cat{Th}$. Let $\phi$ be a $\Sigma$ sentence such that $T'\vdash
f(\phi )$. Thus, $T'\vdash f(\phi )\leftrightarrow f(\psi )$, where
$\psi$ is any $\Sigma$ sentence such that $T\vdash \psi$. Now let
$T''$ be the empty theory in signature $\Sigma ''=\{ p\}$. Define
$g:\Sigma ''\to \mathsf{Sent}(\Sigma )$ by $g(p)=\phi$, and define
$h:\Sigma ''\to \mathsf{Sent}(\Sigma )$ by $h(p)=\psi$. It's easy
to see then that $f\circ g=f\circ h$. Since $f$ is monic, $g=h$,
which means that $T\vdash g(p)\leftrightarrow h(p)$. Therefore,
$T\vdash \phi$, and $f$ is conservative. \end{proof}
\begin{defn} We say that $f:T\to T'$ is \emph{essentially surjective}
just in case for any sentence $\phi$ of $\Sigma '$, there is a
sentence $\psi$ of $\Sigma$ such that $T'\vdash \phi\lra f(\psi
)$. (Sometimes we use the abbreviation ``eso'' for essentially
surjective.) \end{defn}
\begin{prop} If $f:T\to T'$ is essentially surjective, then $f$ is an
epimorphism in $\cat{Th}$. \end{prop}
\begin{proof} Suppose that $f:T\to T'$ is eso. Let
$g,h:T'\rightrightarrows T''$ such that $g\circ f=h\circ f$. Let
$\phi$ be an arbitrary $\Sigma '$ sentence. Since $f$ is eso, there
is a sentence $\psi$ of $\Sigma$ such that $T'\vdash
\phi\leftrightarrow f(\psi )$. But then $T''\vdash g(\phi )\lra
h(\phi )$. Since $\phi$ was arbitrary, $g=h$. Therefore, $f$ is an
epimorphism.
\end{proof}
What about the converse of this proposition? Are all epimorphisms in
$\cat{Th}$ essentially surjective? The answer is Yes, but the result
is not easy to prove. We'll prove it later on, by means of the
correspondence that we establish between theories, Boolean algebras,
and Stone spaces.
%% TO DO -- have we defined equivalence?
\begin{prop} Let $f:T\to T'$ be a translation. If $f$ is conservative
and essentially surjective, then $f$ is a homotopy
equivalence. \end{prop}
\begin{proof} Let $p\in \Sigma '$. Since $f$ is eso, there is some
$\phi _p\in\mathsf{Sent}(\Sigma )$ such that $T'\vdash
p\leftrightarrow f(\phi _p)$. Define a reconstrual $g:\Sigma '\to
\mathsf{Sent}(\Sigma )$ by setting $g(p)=\phi _p$. As usual, $g$
extends naturally to a function from $\mathsf{Sent}(\Sigma ')$ to
$\mathsf{Sent}(\Sigma )$, and it immediately follows that $T'\vdash
\psi \leftrightarrow fg(\psi )$, for every sentence $\psi$ of
$\Sigma '$.
We claim now that $g$ is a translation from $T'$ to $T$. Suppose
that $T'\vdash \psi$. Since $T'\vdash \psi\lra fg(\psi )$, it
follows that $T'\vdash fg(\psi )$. Since $f$ is conservative,
$T\vdash g(\psi )$. Thus, for all sentences $\psi$ of $\Sigma '$,
if $T'\vdash \psi$ then $T\vdash g(\psi )$, which means that
$g:T'\to T$ is a translation. By the previous paragraph,
$1_{T'}\simeq fg$.
It remains to show that $1_T\simeq gf$. Let $\phi$ be an arbitrary
sentence of $\Sigma$. Since $f$ is conservative, it will suffice to
show that $T'\vdash f(\phi )\lra fgf(\phi )$. But by the previous
paragraph, $T'\vdash \psi \lra fg(\psi )$ for all sentences $\psi$
of $\Sigma'$. Therefore, $1_{T}\simeq gf$, and $f$ is a homotopy
equivalence.
\end{proof}
Before proceeding, let's remind ourselves of some of the motivations
for these technical investigations.
The category $\cat{Sets}$ is, without a doubt, extremely useful.
However, a person who is familiar with $\cat{Sets}$ might have
developed some intuitions that could be misleading when applied to
other categories. For example, in $\cat{Sets}$, if there are
injections $f:X\to Y$ and $g:Y\to X$, then there is a bijection
between $X$ and $Y$. Thus, it's tempting to think, for example, that
if there are embeddings $f:T\to T'$ and $g:T'\to T$ of theories, then
$T$ and $T'$ are equivalent. [Here an embedding between theories is a
monomorphism in $\cat{Th}$, i.e.\ a conservative translation.]
Similarly, in $\cat{Sets}$, if there is an injection $f:X\to Y$ and a
surjection $g:X\to Y$, then there is a bijection between $X$ and $Y$.
However, in $\cat{Th}$ the analogous result fails to hold.
\begin{aside} For those familiar with the category $\cat{Vect}$ of
vector spaces: $\cat{Vect}$ is similar to $\cat{Sets}$ in that
mutually embeddable vector spaces are isomorphic. That is, if
$f:V\to W$ and $g:W\to V$ are monomorphisms (i.e.\ injective linear
maps), then $V$ and $W$ have the same dimension, hence are
isomorphic.
The categories $\cat{Sets}$ and $\cat{Vect}$ share in common the
feature that the objects can be classified by cardinal numbers. In
the case of sets, if $|X|=|Y|$, then $X\cong Y$. In the case of
vector spaces, if $\dim (V)=\dim (W)$, then $V\cong W$.
\end{aside}
\begin{prop} Let $f:T\to T'$ be a translation. If $f^*:M(T')\to M(T)$
is surjective, then $f$ is conservative. \end{prop}
\begin{proof} Suppose that $f^*$ is surjective, and suppose that
$\phi$ is a sentence of $\Sigma$ such that $T\not\vdash \phi$. Then
there is a $v\in M(T)$ such that $v(\phi )=0$.\footnote{Here we have
invoked the completeness theorem, but we haven't proven it yet.
Note that our proof of the completeness theorem (page
\pageref{page:complete}) does not cite this result, or any that
depend on it.} Since $f^*$ is surjective, there is a $w\in M(T')$
such that $f^*(w)=v$. But then
\[ w(f(\phi )) = f^*w(\phi ) = v(\phi )=0 ,\] from which it follows
that $T'\not\vdash f(\phi )$. Therefore, $f$ is conservative.
\end{proof}
\begin{example} Let $\Sigma = \{ p_0,p_1,\dots \}$, and let $T$ be the
empty theory in $\Sigma$. Let $\Sigma '=\{ q_0,q_1,\dots \}$, and
let $T'$ be the theory with axioms $q_0\to q_i$, for $i=0,1,\dots$.
We already know that $T$ and $T'$ are not equivalent. We will now
show that there are embeddings $f:T\to T'$ and $g:T'\to T$.
Define $f:\Sigma\to \mathsf{Sent}(\Sigma ')$ by $f(p_i)=q_{i+1}$.
Since $T$ is the empty theory, $f$ is a translation. Then for any
valuation $v$ of $\Sigma '$, we have \[
f^*v(p_i)=v(f(p_i))=v(q_{i+1}) .\] Furthermore, for any sequence of
zeros and ones, there is a valuation $v$ of $\Sigma '$ that assigns
that sequence to $q_1,q_2,\dots $. Thus, $f^*$ is surjective, and
$f$ is conservative.
Now define $g:\Sigma '\to\mathsf{Sent}(\Sigma )$ by setting
$g(q_i)=p_0\vee p_i$. Since $T\vdash p_0\vee p_0\to p_0\vee p_i$,
it follows that $g$ is a translation. Furthermore, for any
valuation $v$ of $\Sigma$, we have
\[ g^*v(q_i) = v(g(q_i)) = v(p_0\vee p_i) .\] Recall that $M(T')$
splits into two parts: (1) a singleton set containing the valuation
$z$ where $z(q_i)=1$ for all $i$, and (2) the infinitely many other
valuations which assign $0$ to $q_0$. Clearly, $z=g^*v$, where $v$
is any valuation such that $v(p_0)=1$. Furthermore, for any
valuation $w$ of $\Sigma '$ such that $w(p_0)=0$, we have $w=g^*v$,
where $v(p_i)=w(q_i)$. Therefore, $g^*$ is surjective, and $g$ is
conservative.
\end{example}
\begin{exercise} In the example above: show that $f$ and $g$ are not
essentially surjective. \end{exercise}
\begin{example} Let $T$ and $T'$ be as in the previous example. Now
we'll show that there are essentially surjective (eso) translations
$k:T\to T'$ and $h:T'\to T$. The first is easy: the translation
$k(p_i)=q_i$ is obviously eso. For the second, define
$h(q_0)=\bot$, where $\bot$ is some contradiction, and define
$h(q_i)=p_{i-1}$ for $i>0$. \end{example}
\begin{disc} Let's pause for just a moment and think about some of the
questions we might want to ask about theories. We arrange these in
roughly decreasing order of technical tractability.
\begin{enumerate}
\item Does $\cat{Th}$ have the \emph{Cantor-Bernstein property}? That
is, if there are monomorphisms $f:T\to T'$ and $g:T'\to T$, then is
there an isomorphism $h:T\to T'$?
\item Is $\cat{Th}$ balanced, in the sense that if $f:T\to T'$ is both
a monomorphism and an epimorphism, then $f$ is an isomorphism?
\item If there is both a monomorphism $f:T\to T'$ and an epimorphism
$g:T'\to T$, then are $T$ and $T'$ homotopy equivalent?
\item Can an arbitrary theory $T$ be embedded into a theory $T_0$ that
has no axioms? \cite{quine-goodman} present a proof of this claim
--- and they argue that it undercuts the analytic-synthetic
distinction. They are right about the technical claim (see
\ref{qgood} below), but have perhaps misconstrued its philosophical
implications.
\item If theories have the same number of models, then are they
equivalent? If not, then can we determine whether $T$ and $T'$ are
equivalent by inspecting $M(T)$ and $M(T')$?
\item How many theories (up to isomorphism) are there with $n$ models?
\item (Supervenience implies Reduction) Suppose that the truth value
of a sentence $\psi$ \emph{supervenes} on the truth value of some
other sentences $\phi _1,\dots ,\phi _n$, i.e., for any valuations
$v,w$ of the propositional constants occurring in
$\phi _1,\dots ,\phi _n,\psi$, if $v(\phi _i)=w(\phi _i)$, for
$i=1,\dots ,n$, then $v(\psi )=w(\psi )$. Does it follow then that
$\vdash\psi \leftrightarrow \theta$, where $\theta$ contains only
the propositional constants that occur in $\phi _1,\dots ,\phi _n$?
(The answer is Yes, as shown by \emph{Beth's theorem}, Section
\ref{go-beth}.)
\item Suppose that $f:T\to T'$ is conservative. Suppose also that
every model of $T$ extends uniquely to a model of $T'$. Does it
follow that $T\cong T'$?
\item Suppose that $T$ and $T'$ are consistent in the sense that there
is no sentence $\theta$ in $\Sigma \cap \Sigma '$ such that $T\vdash
\theta$ and $T'\vdash \neg \theta$. Is there a unified theory $T''$
which extends both $T$ and $T'$? (The answer is Yes, as shown by
\emph{Robinson's theorem}.)
\item What does it mean for one theory to be \emph{reducible} to
another? Can we explicate this notion in terms of a certain sort of
translation between the relevant theories? Some philosophers have
claimed that the reduction relation ought to be treated
semantically, rather than syntactically. In other words, they would
have us consider functions from $M(T')$ to $M(T)$, rather than
translations from $T$ to $T'$. In light of the Stone duality
theorem proved below, it appears that syntactic and semantic
approaches are equivalent to each other.
\item Consider various formally definable notions of theoretical
equivalence. What are the advantages and disadvantages of the
various notions? Is homotopy equivalence too liberal? Is it too
conservative?
\end{enumerate}
\end{disc}
%% To do: Proof of Th <-> Bool and Bool <-> Stone
\section{Boolean algebras} \label{sec:bool}
\begin{defn} A \emph{Boolean algebra} is a set $B$ together with a
unary operation $\neg$, two binary operations $\wedge$ and $\vee$,
and designated elements $0\in B$ and $1\in B$, which satisfy the
following equations:
\begin{enumerate}
\item Top and Bottom \\ $a\wedge 1=a\vee 0=a$
\item Idempotence \\ $a\wedge a=a\vee a=a$
\item De Morgan's rules \\ $\neg (a\wedge b)=\neg a\vee\neg b, \quad \neg
(a\vee b)=\neg a\wedge\neg b$
\item Commutativity \\
$a\wedge b=b\wedge a, \quad a\vee b=b\vee a$
\item Associativity \\
$(a\wedge b)\wedge c=a\wedge (b\wedge c), \quad (a\vee b)\vee c=a\vee (b\vee
c)$
\item Distribution \\ $a\wedge (b\vee c)=(a\wedge b)\vee (a\wedge
c),\quad a\vee (b\wedge c)=(a\vee b)\wedge (a\vee c)$
\item Excluded Middle \\
$a\wedge \neg a=0,\quad a\vee \neg a=1$
\end{enumerate}
Here we are implicitly universally quantifying over $a,b,c$.
\end{defn}
\begin{example} Let $2$ denote the unique Boolean algebra with two
elements $\emptyset$ and $1$. We can think of $2$ as the powerset
of a one-element set $1$, where $\wedge$ is intersection, $\vee$ is
union, and $\neg$ is complement.
Note that $2$ looks just like the truth-value set $\Omega$. Indeed,
$\Omega$ is equipped with operations $\wedge ,\vee$ and $\neg$ that
make it into a Boolean algebra. \end{example}
\begin{example} Let $F$ denote the unique Boolean algebra with four
elements. We can think of $F$ as the powerset of a two-element set,
where $\wedge$ is intersection, $\vee$ is union, and $\neg$ is
complement.
Let $\Sigma = \{ p\}$. Define an equivalence relation $\simeq$ on
sentences of $\Sigma$ by $\phi\simeq\psi$ just in case $\vdash
\phi\lra\psi$. The resulting set of equivalence classes naturally
carries the structure of a Boolean algebra with four
elements. \end{example}
We now derive some basic consequences from the axioms. The first two
results are called the \emph{absorption laws}.
\begin{enumerate}
\item $a\wedge (a\vee b) = a$ \\
\[ a\wedge (a\vee b)=(a\vee 0)\wedge (a\vee b)=a\vee (0\wedge
b)=a\vee 0=a .\]
\item $a\vee (a\wedge b)=a$ \\
\[ a\vee (a\wedge b)=(a\wedge 1)\vee (a\wedge b) = a\wedge (1\vee b)
=a\wedge 1=a . \]
\item $a\vee 1=1$ \\
\[ a\vee 1=a\vee (a\vee \neg a)=a\vee \neg a = 1 . \]
\item $a\wedge 0=0$ \\
\[ a\wedge 0=a\wedge (a\wedge \neg a)=a\wedge\neg a= 0. \] \end{enumerate}
\begin{defn} If $B$ is a Boolean algebra and $a,b\in B$, we write
$a\leq b$ when $a\wedge b=a$. \end{defn}
Since $a\wedge 1=a$, it follows that $a\leq 1$, for all $a\in B$.
Since $a\wedge 0=0$, it follows that $0\leq a$, for all $a\in B$. Now
we will show that $\leq$ is a partial order, i.e.\ reflexive,
transitive, and asymmetric.
\begin{prop} The relation $\leq$ on a Boolean algebra $B$ is a partial
order.
\end{prop}
\begin{proof} (Reflexive) Since $a\wedge a=a$, it follows that $a\leq
a$.
(Transitive) Suppose that $a\wedge b=a$ and
$b\wedge c=b$. Then
\[ \begin{array}{l l} a\wedge c = (a\wedge b)\wedge c = a\wedge
(b\wedge c)=a\wedge b = a, \end{array} \] which means that $a\leq
c$.
(Asymmetric) Suppose that $a\wedge b=a$ and $b\wedge a=b$. By
commutativity of $\wedge$, it follows that $a=b$.
\end{proof}
We now show how $\leq$ interacts with $\wedge,\vee$, and $\neg$. In
particular, we show that if $\leq$ is thought of as implication, then
$\wedge$ behaves like conjunction, $\vee$ behaves like disjunction,
$\neg$ behaves like negation, $1$ behaves like a tautology, and $0$
behaves like a contradiction.
\begin{prop} $c\leq a\wedge b$ iff $c\leq a$ and $c\leq
b$. \end{prop}
\begin{proof} Since $a\wedge (a\wedge b)=a\wedge b$, it follows that
$a\wedge b\leq a$. By similar reasoning, $a\wedge b\leq b$. Thus
if $c\leq a\wedge b$, then transitivity of $\leq$ entails that both
$c\leq a$ and $c\leq b$.
Now suppose that $c\leq a$ and $c\leq b$. That is, $c\wedge a=c$
and $c\wedge b=c$. Then $c\wedge (a\wedge b)=(c\wedge a)\wedge
(c\wedge b)=c\wedge c=c$. Therefore $c\leq a\wedge b$. \end{proof}
Notice that $\leq$ and $\wedge$ interact precisely as implication and
conjunction interact in propositional logic. The elimination rule
says that $a\wedge b$ implies $a$ and $b$. Hence, if $c$ implies
$a\wedge b$, then $c$ implies $a$ and $b$. The introduction rule says
that $a$ and $b$ imply $a\wedge b$. Hence if $c$ implies $a$ and $b$,
then $c$ implies $a\wedge b$.
\begin{prop} $a\leq c$ and $b\leq c$ iff $a\vee b\leq c$ \end{prop}
\begin{proof} Suppose first that $a\leq c$ and $b\leq c$. Then
\[ \begin{array}{l l} (a\vee b)\wedge c = (a\wedge c)\vee (b\wedge
c)=a\vee b .\end{array} \] Therefore $a\vee b\leq c$.
Suppose now that $a\vee b\leq c$. By the absorption law, $a\wedge
(a\vee b)=a$, which implies that $a\leq a\vee b$. By transitivity
$a\leq c$. Similarly, $b\leq a\vee b$, and by transitivity, $b\leq
c$. \end{proof}
Now we show that the connectives $\wedge$ and $\vee$ are monotonic.
\begin{prop} If $a\leq b$ then $a\wedge c\leq b\wedge c$, for any
$c\in B$. \end{prop}
\begin{proof}
\[ \begin{array}{l l l}
(a\wedge c)\wedge (b\wedge c) = (a\wedge b)\wedge c=a\wedge c
.\end{array} \] \end{proof}
\begin{prop} If $a\leq b$ then $a\vee c\leq b\vee c$, for any $c\in
B$. \end{prop}
\begin{proof}
\[ \begin{array}{l l l}
(a\vee c)\wedge (b\vee c) = (a\wedge b)\vee c = a\vee c .\end{array} \]
\end{proof}
\begin{prop} If $a\wedge b=a$ and $a\vee b=a$ then $a=b$. \end{prop}
\begin{proof} $a\wedge b=a$ means that $a\leq b$. We now claim that
$a\vee b=a$ iff $b\wedge a=b$ iff $b\leq a$. Indeed, if $a\vee b=a$
then
$$ b\wedge a = b\wedge (a\vee b)=(0\vee b)\wedge (a\vee b)=(0\wedge
a)\vee b = b .$$
Conversely, if $b\wedge a=b$, then
$$ a\vee b = a\vee (a\wedge b) = (a\wedge 1)\vee (a\wedge b)= a\wedge
(1\vee b) = a .$$ Thus, if $a\wedge b=a$ and $a\vee b=a$, then $a\leq
b$ and $b\leq a$. By asymmetry of $\leq$, it follows that
$a=b$. \end{proof}
We now show that $\neg a$ is the unique complement of $a$ in $B$.
\begin{prop} If $a\wedge b=0$ and $a\vee b=1$ then $b=\neg
a$. \label{unique-complement} \end{prop}
\begin{proof} Since $b\vee a=1$, we have
\[
b = b\vee 0 = b\vee (a\wedge \neg a) = (b\vee a)\wedge (b\vee \neg a)
= b\vee \neg a .\] Since $b\wedge a=0$, we also have
\[ b=b\wedge 1=b\wedge (a\vee \neg a) = (b\wedge a)\vee (b\wedge \neg
a)=b\wedge \neg a .\]
By the preceding proposition, $b=\neg a$.
\end{proof}
\begin{prop} $\neg 1=0$. \end{prop}
\begin{proof} We have $1\wedge 0=0$ and $1\vee 0=1$. By the preceding
proposition, $0=\neg 1$. \end{proof}
\begin{prop} If $a\leq b$ then $\neg b\leq \neg a$. \end{prop}
\begin{proof} Suppose that $a\leq b$, which means that $a\wedge b=a$,
and equivalently, $a\vee b=b$. Thus, $\neg a\wedge \neg b =\neg
(a\vee b)=\neg b$, which means that $\neg b\leq\neg a$. \end{proof}
\begin{prop} $\neg \neg a=a$. \end{prop}
\begin{proof} We have $\neg a\vee \neg\neg a=1$ and $\neg a\wedge \neg
\neg a=1$. By Proposition \ref{unique-complement}, it follows that
$\neg\neg a=a$. \end{proof}
\begin{defn} Let $A$ and $B$ be Boolean algebras. A
\emph{homomorphism} is a map $\phi :A\to B$ such that $\phi (0)=0$,
$\phi (1)=1$, and for all $a,b\in A$, $\phi (\neg a)=\neg \phi (a)$,
$\phi (a\wedge b)=\phi (a)\wedge \phi (b)$ and $\phi (a\vee b)=\phi
(a)\vee \phi (b)$. \end{defn}
It is easy to see that if $\phi :A\to B$ and $\psi :B\to C$ are
homomorphisms, then $\psi\circ \phi :A\to C$ is also a homomorphism.
Moreover, $1_A:A\to A$ is a homomorphism, and composition of
homomorphisms is associative.
\begin{defn} We let $\cat{Bool}$ denote the category whose objects are
Boolean algebras, and whose arrows are homomorphisms of Boolean
algebras. \end{defn}
Since $\cat{Bool}$ is a
category, we have notions of \emph{monomorphisms},
\emph{epimorphisms}, \emph{isomorphisms}, etc.. Once again, it is
easy to see that an injective homomorphism is a monomorphism, and a
surjective homomorphism is an epimorphism.
\begin{prop} Monomorphisms in $\cat{Bool}$ are injective. \end{prop}
\begin{proof} Let $f:A\to B$ be a monomorphism, and let $a,b\in A$.
Let $F$ denote the Boolean algebra with four elements, and let $p$
denote one of the two elements in $F$ that is neither $0$ nor $1$.
Define $\hat{a}:F\to A$ by $\hat{a}(p)=a$, and define $\hat{b}:F\to
A$ by $\hat{b}(p)=b$. It is easy to see that $\hat{a}$ and
$\hat{b}$ are uniquely defined by these conditions, and that they
are Boolean homomorphisms. Suppose now that $f(a)=f(b)$. Then
$f\hat{a}=f\hat{b}$, and since $f$ is a monomorphism,
$\hat{a}=\hat{b}$, and therefore $a=b$. Therefore $f$ is injective.
\end{proof}
It is also true that epimorphisms in $\cat{Bool}$ are surjective.
However, proving that fact is no easy task. We will return to it
later in the chapter.
\begin{prop} If $f:A\to B$ is a homomorphism of Boolean algebras, then
$a\leq b$ only if $f(a)\leq f(b)$. \end{prop}
\begin{proof} $a\leq b$ means that $a\wedge b=a$. Thus,
\[
f(a)\wedge f(b) = f(a\wedge b) = f(a) ,\] which means that $f(a)\leq
f(b)$. \end{proof}
\begin{defn} A homomorphism $\phi :B\to 2$ is called a \emph{state} of
$B$. \end{defn}
\section{Equivalent categories}
We now have two categories on the table: the category $\cat{Th}$ of
theories, and the category $\cat{Bool}$ of Boolean algebras. Our next
goal is to show that these categories are \emph{structurally
identical}. But what do we mean by this? What we mean is that they
are \emph{equivalent categories}. In order to explain what that
means, we need a few more definitions.
%% TO DO: define subalgebra
\begin{defn} Suppose that $\cat{C}$ and $\cat{D}$ are categories. We
let $\cat{C}_0$ denote the objects of $\cat{C}$, and we let
$\cat{C}_1$ denote the arrows of $\cat{C}$. A (covariant)
\emph{functor} $F:\cat{C}\to\cat{D}$ consists of a pair of maps:
$F_0:\cat{C}_0\to\cat{D}_0$, and $F_1:\cat{C}_1\to\cat{D}_1$ with
the following properties:
\begin{enumerate}
\item $F_0$ and $F_1$ are compatible in the sense that if $f:X\to Y$
in $\cat{C}$,then $F_1(f):F_0(X)\to F_0(Y)$ in $\cat{D}$.
\item $F_1$ preserves identities and composition in the following
sense: $F_1(1_X)=1_{F_0(X)}$, and $F_1(g\circ f)=F_1(g)\circ
F_1(f)$.
\end{enumerate}
When no confusion can result, we simply use $F$ in place of $F_0$ and
$F_1$.
\end{defn}
\begin{note} There is also a notion of a \emph{contravariant functor},
where $F_1$ reverses the direction of arrows: if $f:X\to Y$ in
$\cat{C}$, then $F_1(f):F_0(Y)\to F_0(X)$ in $\cat{D}$.
Contravariant functors will be especially useful for examining the
relation between a theory and its set of models. We've already seen
that a translation $f:T\to T'$ induces a function
$f^*:M(T')\to M(T)$. In Section \ref{sec:stone} we will see that
$f\mapsto f^*$ is part of a contravariant functor. \end{note}
\begin{example} For any category $\cat{C}$, there is a functor
$1_{\cat{C}}$ that acts as the identity on both objects and arrows.
That is, for any object $X$ of $\cat{C}$, $1_{\cat{C}}(X)=X$. And
for any arrow $f$ of $\cat{C}$, $1_{\cat{C}}(f)=f$. \end{example}
\begin{defn} Let $F:\cat{C}\to \cat{D}$ and $G:\cat{C}\to \cat{D}$ be
functors. A \emph{natural transformation} $\eta :F\Rightarrow G$
consists of a family $\{ \eta _X:F(X)\to G(X) \mid X\in \cat{C}_0
\}$ of arrows in $\cat{D}$, such that for any arrow $f:X\to Y$ in
$\cat{C}$, the following diagram commutes:
\[ \begin{tikzcd} F(X) \arrow[r,"F(f)"] \arrow[d,"\eta _X"] & F(Y)
\arrow[d,"\eta _Y"]
\\
G(X) \arrow[r,"G(f)"] & G(Y) \end{tikzcd} \] \end{defn}
\begin{defn} A natural transformation $\eta :F\Rightarrow G$ is said
to be a \emph{natural isomorphism} just in case each arrow $\eta
_X:F(X)\to G(X)$ is an isomorphism. In this case, we write $F\cong
G$. \end{defn}
\begin{defn} Let $F:\cat{C}\to \cat{D}$ and $G:\cat{D}\to \cat{C}$ be
functors. We say that $F$ and $G$ are a \emph{categorical
equivalence} just in case $GF\cong 1_{\cat{C}}$ and
$FG\cong 1_{\cat{D}}$. \label{df:cateq} \end{defn}
\section{Propositional theories are Boolean algebras}
In this section, we show that there is a one-to-one correspondence
between theories (in propositional logic) and Boolean algebras. We
first need some preliminaries.
\begin{defn} Let $\Sigma$ be a propositional signature (i.e.\ a set),
let $B$ be a Boolean algebra, and let $f:\Sigma\to B$ be an
arbitrary function. [Here we use $\cap ,\cup$ and $-$ for the
Boolean operations, in order to avoid confusion with the logical
connectives $\wedge ,\vee$ and $\neg$.] Then $f$ naturally extends
to a map $f:\mathsf{Sent}(\Sigma )\to B$ as
follows: \begin{enumerate}
\item $f(\phi\wedge\psi )=f(\phi )\cap f(\psi )$;
\item $f(\phi\vee \psi )=f(\phi )\cup f(\psi )$;
\item $f(\neg \phi) = -f(\phi )$.
\end{enumerate}
Now let $T$ be a theory in $\Sigma$. We say that $f$ is an
\emph{interpretation} of $T$ in $B$ just in case: for all sentences
$\phi$, if $T\vdash \phi$ then $f(\phi )=1$. \end{defn}
\begin{defn} Let $f:T\to B$ be an interpretation. We say that:
\begin{enumerate}
\item $f$ is \emph{conservative} just in case: for all sentences
$\phi$, if $f(\phi )=1$ then $T\vdash\phi$.
\item $f$ \emph{surjective} just in case: for each $a\in B$, there is
a $\phi\in\mathsf{Sent}(\Sigma )$ such that $f(\phi
)=a$. \end{enumerate} \end{defn}
\begin{lemma} Let $f:T\to B$ be an interpretation. Then the following
are equivalent:
\begin{enumerate}
\item $f$ is conservative.
\item For any $\phi ,\psi\in\sg$, if $f(\phi )=f(\psi )$ then
$T\vdash \phi\lra\psi$. \end{enumerate} \end{lemma}
\begin{proof} Note first that $f(\phi )=f(\psi )$ if and only if
$f(\phi\lra \psi)=1$. Suppose then that $f$ is conservative. If
$f(\phi )=f(\psi )$ then $f(\phi\lra\psi )=1$, and hence
$T\vdash\phi\lra\psi$. Suppose now that (2) holds. If $f(\phi
)=1$, then $f(\phi )=f(\phi\vee\neg\phi )$, and hence $T\vdash
(\phi\vee\neg\phi )\lra \phi$. Therefore $T\vdash\phi$, and $f$ is
conservative.
\end{proof}
\begin{lemma} If $f:T\to B$ is an interpretation, and $g:B\to A$ is a
homomorphism, then $g\circ f$ is an interpretation. \end{lemma}
\begin{proof} This is almost obvious. \end{proof}
\begin{lemma} If $f:T\to B$ is an interpretation, and $g:T'\to T$ is a
translation, then $f\circ g:T'\to B$ is an
interpretation. \end{lemma}
\begin{proof} This is almost obvious. \end{proof}
\begin{lemma} Suppose that $T$ is a theory, and $e:T\to B$ is a
surjective interpretation. If $f,g:B\rightrightarrows A$ are
homomorphisms such that $fe=ge$, then $f=g$. \end{lemma}
\begin{proof} Suppose that $fe=ge$, and let $a\in B$. Since $e$ is
surjective, there is a $\phi\in\mathsf{Sent}(\Sigma )$ such that
$e(\phi )=a$. Thus, $f(a)=fe(\phi )=ge(\phi )=g(a)$. Since $a$ was
arbitrary, $f=g$. \end{proof}
Let $T'$ and $T$ be theories, and let $f,g:T'\rightrightarrows T$ be
translations. Recall that we defined identity between translations as
follows: $f=g$ if and only if $T\vdash f(\phi )\lra g(\phi )$ for all
$\phi \in \mathsf{Sent}(\Sigma ')$.
\begin{lemma} Suppose that $m:T\to B$ is a conservative
interpretation. If $f,g:T'\rightrightarrows T$ are translations
such that $mf=mg$, then $f=g$. \end{lemma}
\begin{proof} Let $\phi\in \mathsf{Sent}(\Sigma ')$, where $\Sigma '$
is the signature of $T'$. Then $mf(\phi )=mg(\phi )$. Since $m$ is
conservative, $T\vdash f(\phi )\lra g(\phi )$. Since this holds for
all sentences, it follows that $f=g$.
\end{proof}
\begin{prop} For each theory $T$, there is a Boolean algebra $L(T)$,
and a conservative, surjective interpretation $i_T:T\to L(T)$ such
that for any Boolean algebra $B$, and interpretation $f:T\to B$,
there is a unique homomorphism $\overline{f}:L(T)\to B$ such that
$\overline{f}i_T=f$. \label{lindenbaum} \end{prop}
\[ \begin{tikzcd} T \arrow[r,"i_T"] \arrow[dr,"f"'] & L(T)
\arrow[dashed,d,"\overline{f}"] \\
& B \end{tikzcd} \]
We define an equivalence relation $\equiv$ on the
sentences of $\Sigma$:
\[ \phi \equiv \psi \quad \text{iff} \quad T\vDash \phi\lra\psi ,\]
and we let \[ E_{\phi} \: := \: \{ \psi \mid \phi\equiv \psi \} .\]
Finally, let
\[ L(T) \: := \: \{ E_\phi \mid \phi \in \mathsf{Sent}(\Sigma ) \} .\]
We now equip $L(T)$ with the structure of a Boolean algebra. To this
end, we need the following facts, which correspond to easy proofs in
propositional logic.
\begin{fact} If $E_{\phi}=E_{\phi '}$ and $E_{\psi}=E_{\psi '}$, then:
\begin{enumerate}
\item $E_{\phi\wedge\psi}=E_{\phi '\wedge \psi '}$;
\item $E_{\phi\vee\psi}=E_{\phi '\vee \psi '}$;
\item $E_{\neg \phi}=E_{\neg \phi '}$. \end{enumerate} \end{fact}
\noindent We then define a unary operation $-$ on $L(T)$ by:
\[ -E_{\phi } := E_{\neg \phi } , \] and we define two binary
operations on $L(T)$ by: \[ E_\phi\cap E_\psi := E_{\phi\wedge \psi }
,\qquad E_\phi\cup E_\psi := E_{\phi\vee \psi } .\] Finally, let
$\phi$ be an arbitrary $\Sigma$ sentence, and let
$0=E_{\phi\wedge\neg\phi}$ and $1=E_{\phi\vee\neg\phi}$. The proof
that $\langle L(T),\cap ,\cup ,-,0,1\rangle$ is a Boolean algebra
requires a series of straightforward verifications. For example,
let's show that $1\cap E_\psi =E_\psi$, for all sentences $\psi$.
Recall that $1=E_{\phi\vee\neg \phi}$ for some arbitrarily chosen
sentence $\phi$. Thus,
\[ 1\cap E_\psi \: = \: E_{\phi\vee\neg\phi}\cap E_\psi \: = \:
E_{(\phi\vee\neg\phi)\wedge \psi} .\] Moreover, $T\vdash \psi\lra
((\phi\vee\neg\phi )\wedge \psi )$, from which it follows that
$E_{(\phi\vee\neg \phi )\wedge \psi }=E_\psi$. Therefore, $1\cap
E_\psi=E_\psi$.
Consider now the function $i_T:\Sigma\to L(T)$ given by $i_T(\phi
)=E_\phi$, and its natural extension to $\sg$. A quick inductive
argument, using the definition of the Boolean operations on $L(T)$,
shows that $i_T (\phi )=E_\phi$ for all $\phi\in \mathsf{Sent}(\Sigma
)$. The following shows that $i_T$ is a conservative interpretation
of $T$ in $L(T)$.
\begin{prop} $T\vdash\phi$ if and only if $i_T (\phi )=1$. \end{prop}
\begin{proof} $T\vdash \phi$ iff $T\vdash (\psi\vee\neg\psi )\lra
\phi$ iff $i_T (\phi )=E_\phi=E_{\psi\vee\neg \psi}=1$. \end{proof}
Since $i_T(\phi )=E_\phi$, the interpretation $i_T$ is also
surjective.
\begin{prop} Let $B$ be a Boolean algebra, and let $f:T\to B$ be an
interpretation. Then there is a unique homomorphism
$\overline{f}:L(T)\to B$ such that $\overline{f}i_T=f$. \end{prop}
\begin{proof} If $E_\phi=E_\psi$, then $T\vdash \phi\lra\psi$, and so
$f(\phi )=f(\psi )$. Thus, we may define $\hat{f}(E_\phi )=f(\phi
)$. It is straightforward to verify that $\hat{f}$ is a Boolean
homomorphism, and it is clearly unique.
\end{proof}
\begin{defn} The Boolean algebra $L(T)$ is called the \emph{Lindenbaum
algebra} of $T$. \end{defn}
\begin{prop} Let $B$ be a Boolean algebra. There is a theory $T_B$
and a conservative, surjective interpretation $e_B:T_B\to B$ such
that for any theory $T$, and interpretation $f:T\to B$, there is a
unique interpretation $\overline{f}:T\to T_B$ such that
$e_B\overline{f}=f$. \label{internal} \end{prop}
\[ \begin{tikzcd}
T_B \arrow{r}{e_B} & B \\
T \arrow{ur}[below]{f} \arrow[dashed]{u}{\overline{f}} \end{tikzcd} \]
\begin{proof} Let $\Sigma _B=B$ be a signature. (Recall that a
propositional signature is just a set, where each element represents
an elementary proposition.) We define $e_B:\Sigma _B\to B$ as the
identity, and use the symbol $e_B$ also for its extension to
$\mathsf{Sent}(\Sigma _B)$. We define a theory $T_B$ on $\Sigma _B$
by: $T_B\vdash\phi$ if and only if $e_B(\phi )=1$. Thus,
$e_B:T_B\to B$ is automatically a conservative interpretation of
$T_B$ in $B$.
Now let $T$ be some theory in signature $\Sigma$, and let $f:T\to B$
be an interpretation. Since $\Sigma _B=B$, $f$ automatically gives
rise to a reconstrual $f:\Sigma\to\Sigma _B$, which we will rename
$\overline{f}$ for clarity. And since $e_B$ is just the identity on
$B=\Sigma _B$, we have $f=e_B\overline{f}$.
Finally, to see that $\overline{f}:T\to T_B$ is a translation,
suppose that $T\vdash \phi$. Since $f$ is an interpretation of
$T_B$, $f(\phi )=1$, which means that $e_B(\overline{f}(\phi ))=1$.
Since $e_B$ is conservative, $T_B\vdash \overline{f}(\phi )$.
Therefore, $\overline{f}$ is a translation.
\end{proof}
We have shown that each propositional theory $T$ corresponds to a
Boolean algebra $L(T)$, and each Boolean algebra $B$ corresponds to a
propositional theory $T_B$. We will now show that these
correspondences are functorial. First we show that a morphism $f:B\to
A$ in $\cat{Bool}$ naturally gives rise to a morphism $T(f):T_B\to
T_A$ in $\cat{Th}$. Indeed, consider the following diagram:
\[ \begin{tikzcd}
T_B \arrow{d}{e_B} \arrow[dashed]{r}{T(f)} & T_A \arrow{d}{e_A} \\
B \arrow{r}{f} & A \end{tikzcd} \] Since $fe_B$ is an interpretation
of $T_B$ in $A$, Prop.\ \ref{internal} entails that there is a unique
translation $T(f):T_B\to T_A$ such that $e_AT(f)=fe_B$. The
uniqueness clause also entails that $T$ commutes with composition of
morphisms, and maps identity morphisms to identity morphisms. Thus,
$T:\cat{Bool}\to\cat{Th}$ is a functor.
Let's consider this translation $T(f):T_B\to T_A$ more concretely.
First of all, recall that translations from $T_B$ to $T_A$ are
actually equivalence classes of maps from $\Sigma _B$ to
$\mathsf{Sent}(\Sigma _A)$. Thus, there's no sense to the question,
``which function is $T(f)$?'' However, there's a natural choice of a
representative function. Indeed, consider $f$ itself as a function
from $\Sigma _B=B$ to $\Sigma _A=A$. Then, for $x\in\Sigma _B=B$, we
have
\[ (e_A\circ T(f))(x) = e_A(f(x)) = f(x) = f(e_B(x)) ,\] since $e_A$
is the identity on $\Sigma _A$, and $e_B$ is the identity on $\Sigma
_B$. In other words, $T(f)$ is the equivalence class of $f$ itself.
[But recall that translations, while initially defined on the
signature $\Sigma _B$, extend naturally to all elements of
$\mathsf{Sent}(\Sigma _B)$. From this point of view, $T(f)$ has a
larger domain than $f$.]
A similar construction can be used to define the functor
$L:\cat{Th}\to \cat{Bool}$. In particular, let $f:T\to T'$ be a
morphism in $\cat{Th}$, and consider the following diagram:
\[ \begin{tikzcd}
T \arrow{d}{i_T} \arrow{r}{f} & T' \arrow{d}{i_{T'}} \\
L(T) \arrow[dashed]{r}{L(f)} & L(T') \end{tikzcd} \] Since $i_{T'}f$
is an interpretation of $T$ in $L(T')$, Prop.\ \ref{lindenbaum}
entails that there is a unique homomorphism $L(f):L(T)\to L(T')$ such
that $L(f)i_T = i_{T'}f$.
More explicitly,
\[ L(f)(E_\phi ) \: = \: L(f)(i_T(\phi)) \: = \: i_{T'}f(\phi ) \: =
\: E_{f(\phi )} .\] Recall, however, that identity of arrows in
$\cat{Th}$ is \textit{not} identity of the corresponding functions, in
the set-theoretic sense. Rather, $f\simeq g$ just in case $T'\vdash
f(\phi )\lra g(\phi )$, for all $\phi\in\mathsf{Sent}(\Sigma )$.
Thus, we must verify that if $f\simeq g$ in $\cat{Th}$, then
$L(f)=L(g)$. Indeed, since $i_{T'}$ is an interpretation of $T'$, we
have $i_{T'}(f(\phi ))=i_{T'}(g(\phi ))$; and since the diagram above
commutes, $L(f)\circ i_T=L(g)\circ i_T$. Since $i_T$ is surjective,
$L(f)=L(g)$. Thus, $f\simeq g$ only if $L(f)=L(g)$. Finally, the
uniqueness clause in Prop.\ \ref{lindenbaum} entails that $L$ commutes
with composition, and maps identities to identities. Therefore,
$L:\cat{Th}\to\cat{Bool}$ is a functor.
We will soon show that the functor $L:\cat{Th}\to\cat{Bool}$ is an
equivalence of categories, from which it follows that $L$ preserves
all categorically-definable properties. For example, a translation
$f:T\to T'$ is monic if and only if $L(f):L(T)\to L(T')$ is monic,
etc.. However, it may be illuminating to prove some such facts
directly.
\begin{prop} Let $f:T\to T'$ be a translation. Then $f$ is
conservative if and only if $L(f)$ is injective. \end{prop}
\begin{proof} Suppose first that $f$ is conservative. Let $E_\phi
,E_\psi\in L(T)$ such that $L(f)(E_\phi )=L(f)(E_\psi )$. Using the
definition of $L(f)$, we have $E_{f(\phi )}=E_{f(\psi )}$, which
means that $T'\vdash f(\phi )\lra f(\psi )$. Since $f$ is
conservative, $T\vdash \phi\lra \psi$, from which $E_\phi=E_\psi$.
Therefore, $L(f)$ is injective.
Suppose now that $L(f)$ is injective. Let $\phi$ be a $\Sigma$
sentence such that $T'\vdash f(\phi )$. Since $f(\top )=\top$, we
have $T'\vdash f(\top )\lra f(\phi )$, which means that
$L(f)(E_{\top})=L(f)(E_\phi )$. Since $L(f)$ is injective,
$E_\top=E_\phi$, from which $T\vdash \phi$. Therefore, $f$ is
conservative. \end{proof}
\begin{prop} For any Boolean algebra $B$, there is a natural
isomorphism $\eta _B:B\to L(T_B)$. \end{prop}
\begin{proof} Let $e_B:T_B\to B$ be the interpretation from Prop.\
\ref{internal}, and let $i_{T_B}:T_B\to L(T_B)$ be the
interpretation from Prop.\ \ref{lindenbaum}. Consider the following
diagram:
\[ \begin{tikzcd} T_B \arrow[r,"i_{T_B}"] \arrow[dr,"e_B"'] &
L(T_B) \arrow[dashed,d,"\eta _B"] \\
& B \end{tikzcd} \] By Prop.\ \ref{lindenbaum}, there is a unique
homomorphism $\eta _B:L(T_B)\to B$ such that $e_B=\eta _Bi_{T_B}$.
Since $e_B$ is the identity on $\Sigma _B$,
\[ \eta _B(E_x)=\eta _Bi_{T_B}(x)=e_B(x)=x , \] for any $x\in
B$. Thus, if $\eta _B$ has an inverse, it must be given by the map
$x\mapsto E_x$. We claim that this map is a Boolean homomorphism.
To see this, recall that $\Sigma _B=B$. Moreover, for $x,y\in B$,
the Boolean meet $x\cap y$ is again an element of $B$, hence an
element of the signature $\Sigma _B$. By the defintion of $T_B$, we
have $T_B\vdash (x\cap y)\leftrightarrow (x\wedge y)$, where the
$\wedge$ symbol on the right is conjunction in $\mathsf{Sent}(\Sigma
_B)$. Thus,
\[ E_{x\cap y}=E_{x\wedge y}=E_x\cap E_y .\] A similar argument
shows that $E_{-x}=-E_x$. Therefore, $x\mapsto E_x$ is a Boolean
homomorphism, and $\eta _B$ is an isomorphism.
It remains to show that $\eta _B$ is natural in $B$. Consider the
following diagram:
\[ \begin{tikzcd} T_B \arrow{rr}{T_f} \arrow{dr}{e_B}
\arrow{ddr}[below]{i_{T_B}} & & T_A
\arrow{dr}{e_A} \arrow{ddr}[below]{i_{T_A}} \\
& B \arrow{rr}{f} & & A \\
& L(T_B) \arrow[u,"\eta _B"'] \arrow{rr}{LT(f)} & & L(T_A) \arrow[u,"\eta _A"'] \end{tikzcd} \] The top square
commutes by the definition of the functor $T$. The triangles on the
left and right commute by the definition of $\eta$. And the outmost
square commutes by the definition of the functor $L$. Thus we have
\[ \begin{array}{l l l}
f\circ \eta _B\circ i_{T_B} & = & f\circ e_B \\
& = & e_A\circ T_f \\
& = & \eta _A\circ i_{T_A}\circ T_f \\
& = & \eta _A\circ LT(f)\circ i_{T_B} .
\end{array} \] Since $i_{T_B}$ is
surjective, it follows that $f\circ \eta _B=\eta _A\circ LT(f)$, and
therefore $\eta$ is a natural transformation.
\end{proof}
\begin{disc} Consider the algebra $L(T_B)$, which we have just proved
is isomorphic to $B$. This result is hardly surprising. For any
$x,y\in \Sigma _B$, we have $T_B\vdash x\lra y$ if and only if
$x=e_B(x)=e_B(y)=y$. Thus, the equivalence class $E_x$ contains $x$
and no other element from $\Sigma _B$. [That's why $\eta _B(E_x)=x$
makes sense.] We also know that for every
$\phi\in\mathsf{Sent}(\Sigma _B)$, there is an $x\in \Sigma _B=B$
such that $T_B\vdash x\lra \phi$. In particular, $T_B\vdash
e_B(\phi)\lra \phi$. Thus, $E_\phi=E_x$, and there is a natural
bijection between elements of $L(T_B)$ and elements of $B$.
\end{disc}
\begin{prop} For any theory $T$, there is a natural isomorphism
$\varepsilon _T:T\to T_{L(T)}$. \end{prop}
\begin{proof} Consider the following diagram:
\[ \begin{tikzcd}
T_{L(T)} \arrow{r}{e_{L(T)}} & L(T) \\
T \arrow[dashed]{u}{\varepsilon _T} \arrow{ur}[below]{i_T}
\end{tikzcd} \] By Prop.\ \ref{internal}, there is a unique
interpretation $\varepsilon _T:T\to T_{L(T)}$ such that
$e_{L(T)}\varepsilon _T=i_T$. We claim that $\varepsilon _T$ is an
isomorphism. To see that $\ve _T$ is conservative, suppose that
$T_{L(T)}\vdash \ve _T(\phi )$. Since $e_{L(T)}$ is an
interpretation, $e_{L(T)}\ve _T (\phi )=1$ and hence $i_T(\phi )=1$.
Since $i_T$ is conservative, $T\vdash \phi$. Therefore $\ve _T$ is
conservative.
To see that $\ve _T$ is essentially surjective, suppose that $\psi\in
\mathsf{Sent}(\Sigma _{L(T)})$. Since $i_T$ is surjective, there is a
$\phi\in \mathsf{Sent}(\Sigma )$ such that $i_T(\phi )=e_{L(T)}(\psi
)$. Thus, $e_{L(T)}(\ve _T(\phi ))=e_{L(T)}(\psi )$. Since
$e_{L(T)}$ is conservative, $T_{L(T)}\vdash \ve _T(\phi)\lra \psi$.
Therefore, $\ve _T$ is essentially surjective.
It remains to show that $\ve _T$ is natural in $T$. Consider the
following diagram:
\[ \begin{tikzcd}
T \arrow{d}[left]{\ve _T} \arrow{rr}{f} \arrow{ddr}{i_T} & & T'
\arrow{d}{\ve _{T'}} \arrow{ddr}{i_{T'}} \\
T_{L(T)} \arrow{rr}{TL(f)} \arrow{dr}[left]{e_{L(T)}} & & T_{L(T')}
\arrow{dr}[left]{e_{L(T')}} \\
& L(T) \arrow{rr}{L(f)} & & L(T') \end{tikzcd} \]
The triangles on the left and the right commute by the definition of
$\ve$. The top square commutes by the definition of $L$, and the
bottom square commutes by the definition of $T$. Thus, we have
\[ \begin{array}{l l l} e_{L(T')}\circ \ve _{T'}\circ f & = & i_{T'}\circ f \\
& = & L(f)\circ i_T \\
& = & L(f)\circ e_{L(T)}\circ \ve _T \\